Legal Status of Cryptocurrency Circulation in Iraq: Lessons from the United Arab Emirates and the United States - Ghassan Adhab Atiyah; Nazura Abdul Manap; Saidatul Nadia Abd Aziz (Hasanuddin Law Review, 2023)
The philosophical emergence of cryptocurrencies is a consequence of the desire to get rid of the authorities’ control of the monetary system, which encouraged people to deal with it for investment or to facilitate the fulfilment of their financial obligations. The research problem is represented through the lack of legislation that regulates dealing with cryptocurrencies in Iraq. There are many technical, legal, and security risks for the use and circulation of cryptocurrency, which must be legally addressed and suitable solutions found. Therefore, this article aims to examine and analyse the legal status of cryptocurrencies in selected jurisdictions through multiple stages, from prohibition to licensing and regulation. This article adopted a qualitative approach to analyse the legal status of cryptocurrency in the selected jurisdictions. The study finding shows that the Iraqi authorities do not have the technical or legal means to prevent the illegal use of cryptocurrencies. In addition, there is a large legislative gap with the developed countries, and lawmakers need to regulate cryptocurrencies by enacting laws to protect people from falling victim to fraud.